Implementation of the Hill Climbing Method determines the shortest path to the Tanah Datar Regency tourist attraction - Rika Widya Perdana (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Searching is a method in the best search to find a solution. The heuristic search method is the most common and most widely used method in the process of finding the shortest path to find a solution. The process of completing searching using the Hill Climbing method, this method uses a heuristic function. The problem in this case is solving the problem of finding the best path to save costs and time in visiting recreational areas in the Batu Sangkar area, Tanah Datar Regency. The advantage of this algorithm is that all possible solutions will be obtained and then checked from the left side one by one, so that a solution with optimal results will be obtained. In its application, the Hill Climbing method uses Geographic Information Systems as a tool in making decisions, by collecting, examining, and analyzing information related to digital maps. with the combination of the Hill Climbing method and geographic information systems can produce an application that can overcome the problem of finding the shortest path.